PENGARUH DEVIDEN PER SHARE, RETURN ON EQUITY DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PERUSAHAAN JASA KONSTRUKSI YANG TERCATAT DI BURSA EFEK INDONESIA (PERIODE 2017-2019) - Septi, Regita Hana; Jayanti, Esih; Zamroni (JURNAL EKONOMI, 2022)
This study aims to examine the effect of dividends per share, return on equity, and net profit margin on stock prices listed on the Indonesia stock exchange. The sample in this study was 15 companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The results of this study were collected through secondary data from the source www.idx.co.id and analyzed using multiple linear regression analysis. This research method was carried out by purposive sampling. The data quality test used in this study is descriptive statistics. To test the hypothesis in this study using the t test and f test. The data obtained from the research results show that dividend per share has no significant effect on the stock price of construction service companies listed on the Indonesia Stock Exchange for the period 2017-2019 with tcount <ttable = 1.708 <2.019 and a sig value of 0.095> 0.005. Return On Equity has no significant effect on the Stock Price of Construction Service Companies listed on the Indonesia Stock Exchange for the period 2017-2019 with tcount <ttable = -1.491 <2.019 and sig value 0.144> 0.005. Net Profit Margin has a significant effect on the Stock Price of Construction Service Companies listed on the Indonesia Stock Exchange for the period 2017-2019 with tcount <ttable = -2.427> 2.019 and asig value of 0.020 <0.005. and Dividend Per Share, Return On Equity, and Net Profit Margin have a significant effect on the Stock Price of Construction Service Companies listed on the Indonesia Stock Exchange for the period 2017-2019 with fcount> ftabel = 3.301> 2.83 and a sig value of 0.030 <0.005.